P-009 Rapidly Progressive Intracranial Infectious Aneurysms; A Case Report and Literature Review. (14th July 2013) - Walsh, K; Bain, M
Abstract : Background: Intracranial infectious aneurysms are difficult to treat cerebrovascular lesions that are typically caused by bacterial infection of the vessel wall, and have been shown to present after acute rupture or ischaemia. They are commonly due to haematogenous spread from a proximal source, but can also be secondary to direct spread from a nearby intracranial source. These lesions have been associated with a mortality rate of nearly 30%. Previous studies have indicated that infiltration of microorganisms into the vessel wall can lead to loss of vessel wall integrity and eventual aneurysm or pseudoaneurysm formation. Septic emboli from a proximal source can also lead to arterial occlusion and infarction, which can be followed by abscess formation within the infarcted tissue. There is no widely accepted management strategy for these lesions, however previous studies have supported the use of antibiotic therapy with or without surgical or endovascular intervention. Case Description: Patient is a 41 y/o male who presented with a HH2 F2 subarachnoid haemorrhage in the setting of Coumadin use (INR 9.0 upon presentation) for his history of CHF treated with LVAD placement. He had been having fevers, diarrhoea, and abdominal pain for 3–5 days prior to presentation. Blood cultures grew MRSA. Diagnostic cerebral angiography on post-bleed day 1 revealed no source for his haemorrhage but did show areas of subocclusive thrombus in the L distal MCA and ACA territories. On post-bleed day 2, patient suffered a new L frontal operculum intraparenchymal haemorrhage. Repeat angiography performed forty-eight hours after the initial study revealed a left M3 fusiform aneurysm and L pericallosal artery aneurysm that arose from areas adjacent to prior subocclusive thrombus, but were not amenable to endovascular therapy. He continued to deteriorate clinically from a cardiopulmonary standpoint, and his family withdrew care on post-bleed day 6. Literature Review and Discussion: There is no widely accepted management strategy for these lesions due to their rarity and a lack of population based studies regarding their natural history and clinical course. Antibiotic therapy, with or without surgical or endovascular intervention, has been supported by the available literature. Studies have reported a wide range of responses to conservative management with antibiotics alone.In our literature review, no studies were identified that demonstrated such a rapid progression and aggressive clinical course as described in this particular case presentation. The rapid development of aneurysm formation from an area that previously demonstrated angiographic evidence of subocclusive thrombus is a finding that has not yet been described in the literature. The speed at which this progression occurred has also not yet been described. It raises the question of whether or not the virulence of the organism impacts the overall progression of the lesion, and if so, should treatment strategies be adjusted based on the organism involved? This case validates the need for aggressive management using a combination of antibiotic therapy as well as endovascular or open neurosurgical intervention. Disclosures: K. Walsh: None. M. Bain: None.